Probation pracademics: Protectors of the ‘honourable profession’? - Ainslie, Samantha (Probation journal, 2025)
This article attempts to widen the debate about the future of probation by way of an exploration of the role of probation pracademics within the context of the Professional Qualification in Probation (PQiP). Reflecting upon our own experiences of probation education (as former probation practitioners, now PQiP tutors and probation researchers), we draw upon transformative pedagogy to argue that pracademics are ideally placed to influence and shape the future of probation as a distinct occupation by enactment of three crucial functions within probation education: (re)formulation of probation values, building bridges between theory and praxis and protection of the ‘honourable profession’.